Modelling and simulating exit selection during assisted hospital evacuation process using fuzzy logic and unity3D - Mohammad Abir, Intiaz; Ali Moustafa Allam, Ali Ahmed; Mohd Ibrahim, Azhar (Science and Information Organization, 2021)
Evacuation procedures are an integral aspect of the emergency response strategy of a hospital. Evacuation simulation models help to properly evaluate and improve evacuation strate- gies. However, the issue of exit selection during evacuation is often overlooked and oversimplified in the evacuation simulation models. Moreover, most of the available evacuation simulation models lack integration of movement devices and assisted evacu- ation features. However, finding a solution of these limitations is a necessity to properly evaluate evacuation strategies. To tackle this problem, we propose an effective approach to model exit selection using a fuzzy logic controller (FLC) and simulate assisted hospital evacuation using Unity3D game engine. Our research demonstrates that selecting exits based on distance only is not sufficient for real life situation because it ignores the unpredictability of human behavior. On the contrary, the use of the proposed FLC for exit selection makes the simulation more realistic by addressing the uncertainty and randomness in an evacuee’s decision-making process. This research can play a vital role in future developments of evacuation simulation models.